Integrated information center at Faculty of Communication, Vilnius University - Kojelytė, Giedrė; Bagdonavičius, Vaidotas (Information & Media, 1997)
Nowadays information service provision and generation of information become the main activity indicator of economical, social, political and cultural potency of society.Rapidly changing information and technical environment of modern society basically makes influence on various organisation types of activity. Knowledge workers become dominating work power, information - strategic resource of knowledge workers' activity, information technologies - the main work utility, which guarantees efficiency of activities and success of organisation.Traditional information systems are not capable keeping the rate of changes and ensuring access to all kinds of information resources, providing modern information services. Therefore the need for new quality information service in academical environment turns up. Integrated Information Center established at Faculty of Communication, Vilnius University in an attempt to provide information services congruent to academical needs.
Keywords: -